Pendidik sebagai Fasilitator dalam Pembelajaran Bab Banyu Kitab Fathul Muin: Perspektif Al-Qur’an Hadis - Ma'arif, Samsul (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
This article examines the urgency of teaching fiqh thaharah, particularly the Bab Banyu, within the tradition of pesantren education that is grounded in practical learning and the natural environment. This topic is important because fiqh instruction in pesantren is not limited to textual understanding but also emphasizes the internalization of values of purity, cleanliness, and moral responsibility in students’ daily lives. The study aims to analyze the role of educators as facilitators and the use of the river at Pondok Pesantren Ringinagung as a contextual medium for learning thaharah. This research employs a qualitative field study approach. Data were collected through observation, in-depth interviews with the kiai and pesantren administrators, and documentation, and were analyzed descriptively and analytically. The findings indicate that learning Bab Banyu is carried out through direct purification practices, habitual environmental cleanliness, and the exemplary role of educators, enabling thaharah values to be experienced rather than merely understood normatively. This study highlights the importance of integrating fiqh texts, Qur’anic values, and empirical experience in pesantren education.